2009
DOI: 10.1126/science.1166862
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Formation of Sharp Zigzag and Armchair Edges in Graphitic Nanoribbons

Abstract: Graphene nanoribbons can exhibit either quasi-metallic or semiconducting behavior, depending on the atomic structure of their edges. Thus, it is important to control the morphology and crystallinity of these edges for practical purposes. We demonstrated an efficient edge-reconstruction process, at the atomic scale, for graphitic nanoribbons by Joule heating. During Joule heating and electron beam irradiation, carbon atoms are vaporized, and subsequently sharp edges and step-edge arrays are stabilized, mostly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
561
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 675 publications
(592 citation statements)
references
References 28 publications
25
561
2
4
Order By: Relevance
“…Zigzag and armchair are two main types of edges along the crystallographic directions in graphene. In recent years, extensive studies were carried out to investigate the relative stability of these two edge orientations and the edge orientation-dependent physics for mechanically exfoliated monolayer graphene flakes [7274], epitaxial graphene islands [7577], CVD derived graphene grains [78], and graphene nanoribbons (GNRs) [7981]. …”
Section: The Structure Of Graphenementioning
confidence: 99%
See 2 more Smart Citations
“…Zigzag and armchair are two main types of edges along the crystallographic directions in graphene. In recent years, extensive studies were carried out to investigate the relative stability of these two edge orientations and the edge orientation-dependent physics for mechanically exfoliated monolayer graphene flakes [7274], epitaxial graphene islands [7577], CVD derived graphene grains [78], and graphene nanoribbons (GNRs) [7981]. …”
Section: The Structure Of Graphenementioning
confidence: 99%
“…(Z: zigzag; A: armchair) [78]. (f) A modified HRTEM image of overlapping zigzag-armchair edges; the HRTEM image is originally from Ref [79], and the modified version is from Ref [111] (reused with permissions from [78] Copyright © 2011, Springer Nature, [79] Copyright © 2009, American Association for the Advancement of Science, and [111] Copyright © 2010 Elsevier Ltd.). …”
Section: The Structure Of Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…These are two most seen edge structures after Joule heating of graphene 187. The chiral‐GNR (CGNR) is composed by a combination of armchair and zigzag sites.…”
Section: Looking Beyond Catalysts: Edges Of Graphenementioning
confidence: 99%
“…[31][32][33][34][35][36] A comprehensive review on the properties and synthesis of GNRs has been reported elsewhere. [ 37 ] Jia et al [ 38 ] noted that when using Joule heating and high electron irradiation, the most stable edges in graphene ribbons are either zigzag or armchair edges. At present, it is important to device GNRs and GNPs exhibiting sharp and crystalline edges so that specifi c polymer reactions could be controlled.…”
Section: Structure and Physico-chemical Properties Of Graphenementioning
confidence: 99%